EFEKTIFITAS DIFERENSIASI LEARNING DALAM PENDIDIKAN AGAMA ISLAM TERHADAP PENINGKATAN PEMAHAMAN KOGNITIF PESERTA DIDIK DI SDN 1 ASRIKATON KABUPATEN MALANG: The Effectiveness of Differentiated Learning Styles in Islamic Religious Education on Improving Students' Cognitive Understanding at SDN 1 Asrikaton Malang Regency - Putri Wahyuni (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
Students at Asrikaton 1 Elementary School in Malang Regency exhibit diverse learning needs shaped by family background and environment, making learning style differentiation crucial. This study aims to analyze how learning style differentiation in Islamic Religious Education (PAI) influences students' cognitive understanding. A quantitative approach was used, correlating learning style differentiation with cognitive achievement. The population included 173 students, with 115 samples. Data were tested for validity and reliability, and analyzed through normality, linearity, and hypothesis testing using SPSS. The results indicate that differentiation has a positive impact on students' cognitive understanding. Hypothesis testing yielded a significance value below 0.05, meaning the alternative hypothesis—learning style differentiation is effective in PAI—is accepted while the null hypothesis is rejected. Cognitive understanding increased by an average of 26.3%, indicating that tailored instruction supports better understanding. This study highlights the importance of tailoring instruction to students' diverse learning styles for improved outcomes. However, there are several limitations, particularly the failure of the validity test that may have led to the underrepresentation of certain research indicators, requiring caution in interpreting the findings. Overall, this research supports the role of differentiation strategies in improving student performance, especially in subjects that require conceptual understanding such as Islamic Religious Education. Peserta Didik di Sekolah Dasar Negeri (SDN) 1 Asrikaton Kabupaten Malang, menunjukkan kebutuhan belajar beragam yang dibentuk oleh latar belakang keluarga dan lingkungan, sehingga diferensiasi gaya belajar menjadi penting. Penelitian ini bertujuan menganalisis bagaimana diferensiasi gaya belajar dalam Pendidikan Agama Islam (PAI) memengaruhi pemahaman kognitif siswa. Pendekatan kuantitatif digunakan, yang mengkorelasikan diferensiasi gaya belajar dengan pencapaian kognitif. Populasi mencakup 173 siswa, dengan 115 sampel. Data diuji validitas, reliabilitas, dan dianalisis melalui uji normalitas, linearitas, dan hipotesis menggunakan SPSS. Hasil menunjukkan bahwa diferensiasi memiliki dampak positif pada pemahaman kognitif siswa. Pengujian hipotesis menghasilkan nilai signifikansi di bawah 0,05, yang berarti hipotesis alternatif—diferensiasi gaya belajar efektif dalam PAI—diterima sementara hipotesis nol ditolak. Pemahaman kognitif meningkat rata-rata 26,3%, yang menunjukkan bahwa pengajaran yang disesuaikan mendukung pemahaman yang lebih baik. Penelitian ini menyoroti pentingnya menyesuaikan instruksi dengan berbagai gaya belajar siswa untuk hasil yang lebih baik. Meskipun demikian, terdapat beberapa keterbatasan, terutama kegagalan uji validitas yang mungkin menyebabkan indikator penelitian tertentu kurang terwakili, sehingga memerlukan kehati-hatian dalam menafsirkan temuan. Secara keseluruhan, penelitian ini mendukung peran strategi diferensiasi dalam meningkatkan kinerja siswa, terutama dalam mata pelajaran yang membutuhkan pemahaman konseptual seperti PAI. Kata Kunci : Gaya Belajar; Pemahaman Kognitif; Pembelajaran Berdiferensiasi; Pendidikan Agama Islam.